Errores de medicación en pediatría (2021)
ABSTRACT: Medication errors (ME) are preventable incidents of inappropriate use of medications by health personnel or by the patient. These events can occur at any stage of drug use generating significant costs to the health system and, in some cases, these can even lead to death. The pediatric population is considered susceptible to ME with a prevalence 3 times higher than adult patients. Objective: To identify the prevalence of medication errors in hospitalized pediatric patients, as well as their classification according to the stage of use of the medication when they occurred. Method: A literature review of ME in pediatrics was carried out through a Pubmed / Medline search using Mesh terms (“Medication Errors” and “Pediatrics”) in the last 10 years. Three investigators reviewed independently the identified articles considering the STROBE checklist for observational studies. Results: 192 bibliographic references were identified, 22 of them were eligible for review and data collection. Studies reported an error rate between 1% and 58% of the evaluated medication indications, with errors reported in different processes of drug use. 9 articles (41%) described errors related only to prescription, mainly associated with incorrect dosage, 6 (27%) errors related to prescription, administration, and other processes, 3 (14%) related to prescription and administration, 2 (9%) related only to administration, 1 (4%) article reported errors related to conciliation, and 1 (4%) described errors related to preparation and administration. Conclusion: The studies reported different medication errors in the pediatric population. Most of them reported ME related to prescription followed by ME in the administration. Knowing the proportion of ME allows focusing interventions aimed at reducing their prevalence.